Agroproductive response of Zea mayz L. with the foliar application of VIUSID agro® - Peña, Kolima; Calero-Hurtado, Alexander; Olivera-Viciedo, Dilier; Rodríguez, Juan Carlos; Fernandes, Thiago; García, Rainel; Ajila, Gabriela (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Growth promoters can be an alternative to increase the growth and production of crops of agricultural importance such as corn. To determine the effect of VIUSID agro® on the agroproductive response of corn, two experiments were designed in consecutive years. In both, a randomized block experimental design was carried out to evaluate four treatments, VIUSID agro® (0.1, 0.3 and 0.5 L.ha−1) and a control, with three replications. Different variables of the growth and development of the crop, including agricultural yield were evaluated. The best performance doses in the several variables of two experiments were 0.3 and 0.5 L.ha−1. The treatments with the best performance in the agricultural yield in both experiments were the doses 0.3 and 0.5 L.ha−1 with an average increase compared to the control of 24.55 and 45.06 % respectively. Therefore, VIUSID agro® favored the agro−productive response of corn.